Competências pessoais e sociais em contexto pré-escolar - Ferreira, Marco (2017)
This study was prepared under the Course of Supervised Teaching Pratice, having as a purpose to obtain a Master’s Degree in Qualification for Teaching in Preschool Education and Teaching of the 1st cycle of basic education. The subject under study is the importance of personal and social skills in pre-school context. Research has as participants the theacher na the group of children and the study design considered most appropriate was the case study. Following bellow are the starting questions: - What is importance of pre-school for the education of children? - What is the contribution of the teacher to the child’s development? - How importante is the relationship between educator/child? This study’s main objectives are: 1) To know the importance of pre-school for children of the teaching-learning process; 2) To recognize and understand the impact that the educator has on children; 3) To know the importance of relationship between the educator/child for emotional development of the child. The information collection method is based on naturalistic observations of the teacher and the group of children in the contexto of the room, which latter will be analyzes and interpreted. These observations took place in a private institution in the municipality of Lisbon.